Trends and Cross-National Differences in Educational Homogamy in Europe: The Role of Educational Composition - Uunk, Wilfred (Comparative population studies, 2024)
The extent of educational homogamy has important consequences for social inequalities and social cohesion. However, little is known about current trends, cross-national differences, and the drivers of educational homogamy in Europe. This study aims to fill this gap by (a) describing trends in absolute educational homogamy (i.e., the share of similarly educated partners) and relative educational homogamy (i.e., homogamy corrected for the distribution of spouses’ education) for European countries; and (b) examining the association between a population’s educational composition and the level of absolute and relative educational homogamy. Given the large changes in the educational composition of European populations and the presumed consequences for absolute and relative educational homogamy, this focus on educational composition is warranted. Our aggregate-level regression analyses covering 36 countries and five birth cohorts (1940-1989) from the European Social Survey show that absolute and relative educational homogamy has not changed. However, this obscures variation by education group and country. We find that the extent of absolute educational homogamy in a country cohort is strongly associated with educational composition and observe statistical effects of educational expansion (positive for the higher educated), educational heterogeneity (negative), educational gender symmetry (positive), educational income inequality (positive), and educational reproduction (positive). Relative educational homogamy is only weakly associated with a population’s educational composition, and its effects are confined to gender symmetry (positive) and educational reproduction (positive). Our findings suggest that changes in educational composition in Europe affect educational homogamy in various directions and indicate that these effects come from structural opportunities rather than changing preferences for educational homogamy. * This article belongs to a special issue on “Changes in Educational Homogamy and Its Consequences”.